Combined Sugarcane Pretreatment for the Generation of Ethanol and Value-Added Products - Bordignon, Sidnei Emilio [UNESP]; Ximenes, Eduardo; Perrone, Olavo Micali [UNESP]; Carreira Nunes, Christiane da Costa [UNESP]; Kim, Daehwan; Boscolo, Maurício [UNESP]; Gomes, Eleni [UNESP]; Filho, Edivaldo Ximenes Ferreira; da Silva, Roberto [UNESP]; Ladisch, Michael R. (Frontiers, 2022)
In this work, we have tested individual and combination of applications of ozonolysis and liquid hot water (LHW) to pretreat sugarcane bagasse (SCB) for the removal of enzyme and/or microbial inhibitors and generation of potential value-added chemicals. A solid content with 80% cellulose and a liquid phase (liquor) rich in phenolic derived compounds (3 g.L−1) from lignin, sugars (>20 g.L−1), and other compounds, such as furfural and hydroxymethylfurfural (HMF), were generated. Maximal (59%) glucan conversion occurred in the presence of double-pretreated bagasse, which had 32–50% more glucan available than the samples that were individually LHW or ozone-pretreated, resulting in maximal ethanol production (92% after 42 h) from double-pretreated SCB enzyme hydrolyzate. In summary, this work showed that ozone reacts effectively with lignin without the use of any other chemical reagent, and LHW pretreatment, followed by a washing step, was effective in solubilizing and cleaning up the fiber enzyme and microbial inhibitory compounds with ozone being effective against phenolics. Moreover, the generated cellulose-rich substrate is readily fermentable. The acidic liquor fraction removed by sequential washings and containing mainly sugars and phenolic compounds may be evaluated for use in green chemistry bioconversions processes.
Keywords: enzyme hydrolysis; ethanol fermentation; inhibitors; liquid hot water; ozone; pretreatment; value-added chemicals